Una investigación teatral y fílmica sobre el trabajo: Algunas obras de Gerardo Naumann - Contreras, Sandra Claudia (2019)
This paper is a reading of Gerardo Naumann’s plays and films shown as a theatrical and performative investigation into the world of labor (his plays Los trabajos improductivos andFábrica,and his films El trabajo industrial and Ricardo Bar). Our approach is based on three hypotheses: 1) Naumann's nonproductive labors (stealing, acting) explore and exhibit virtuosity—i.e. the articulation between memory, repetition and the use of words--as a field of experimentation; 2) by displacing performers from their social location (their status of workers, indistrial or nonproductive workers), Nauman’s theatrical experimentation with the worker-performers’ voices is both a political experimentation as well as an inquiry into new forms of community and subjectivation; 3) Naumann's vital involvement in his own performances playing a worker establishes a frame of reference so that the exploration of the world of labor becomes the (ambivalent) register of the “bargaining” position of artists with non-actors, nonproductive workers, and worker actors.